SISTEM MONITORING DAN KONTROL PINTU BERBASIS ESP32-CAM DAN SENSOR ULTRASONIK - Sudrajat, Jajat; Tisnawati, Rini; Wirahadi, Umar (POLITEKNIK PIKSI GANESHA, 2025)
The development of technology has encouraged the creating a more efficient and secure door security system. This study designs and implements an automatic door monitoring and control system based on the ESP32-CAM microcontroller and ultrasonic sensors. This system is designed to detect the presence of objects or people in front of the door using the HC-SR04 ultrasonic sensor. The ESP32-CAM module is used to send images or videos in real time to the user's device via a Wi-Fi connection to be displayed on the LCD screen, and allows remote monitoring. In addition, the system is equipped with a manual control feature via a web-based application. The test results show that the system is able to respond quickly to object detection at a certain distance, and provide adequate visual monitoring quality in a local network. This system is expected to improve comfort, security, and efficiency in managing automatic door access, especially in private environments and public facilities.